Evaluating The Quality Of Educational Service From The Perspective Of Students Of The Faculty Of Economics At Tishreen University - عباس نيروز; بسام زاهر; وسيم جبور (Latakia University Journal - Economic and Legal Sciences Series, 2025)
The research aimed to identify the level of quality of educational service provided from the point of view of students of the Faculty of Economics at Tishreen University، through studying the reality and knowing the relative importance of the dimensions of quality of educational service (tangibility، responsiveness، safety، reliability، empathy) in the university under study. The researcher relied on the descriptive approach as a general approach to the research، and the researcher distributed the questionnaire to (290) individuals from the study community. The results concluded that there are significant differences between the level of dimensions of quality of educational services currently prevailing in the university under study، and the level of dimensions of quality of educational services that must be available from the point of view of students of the Faculty of Economics. Then the study presented some recommendations، the most important of which were:. Paying attention to research that aims to reveal the aspects contributing to the development of educational service and its level of quality and the extent of its impact on students’ opinions and desires، and working to develop it in light of the results of this research. Paying attention to research and studies on students’ expectations regarding the quality of educational services، and working to measure the gap between what is expected and what is perceived.